Analytical Study of Particle Geodesics Around a Scale-Dependent de Sitter Black Hole - Fathi, M (Academic Press, 2023)
We give a fully analytical description of radial and angular geodesics for massive particles that travel in the spacetime provided by a (3+1)-dimensional scale-dependent black hole in the cosmological background, for which, the quantum corrections are assumed to be small. We show that the equations of motion for radial orbits can be solved by means of Lauricella hypergeometric functions with different numbers of variables. We then classify the angular geodesics and argue that no planetary bound orbits are available. We calculate the epicyclic frequencies of circular orbits at the potential s maximum and the deflection angle of scattered particles is also calculated. Finally, we resolve the raised Jacobi inversion problem for the angular motion by means of a genus-2 Riemannian theta function, and the possible orbits are derived and discussed. © 2023 Elsevier Inc.